Feeding Value of Extracted Coconut Meal for White Leghorn Layers - Moorthy, M.; Viswanathan, K. (International Journal of Poultry Science, 2006)
An experiment was conducted to study the effect of extracted coconut meal (ECM) on egg production performance, egg quality, carcass characteristics and biochemical parameters from 21 to 52 weeks in one hundred and eighty Single Comb White Leghorn (SCWL) layers. These birds were randomly grouped into five treatments with three replicates of twelve birds each. The treatment groups consisted of 0 (T1), 5 (T2), 10 (T3), 15 (T4) and 20 percent (T5) coconut meal inclusion in the egg type chicken diet. The results revealed that five percent coconut meal fed group showed significantly (P< 0.01) higher body weight when compared to other coconut meal fed groups but it was comparable to control at 52 weeks of age. No significant difference was observed in overall mean feed consumption, feed conversion ratio and livability during the experimental period. Both overall hen housed and hen day egg production significantly (P< 0.05) reduced in T5 compared to other treatment groups. Based upon this study, it is recommended to include the coconut meal up to 10 percent in egg type ration for better egg production.